A thematic analysis on the social conditions reflected in Bangsamoro literary pieces - Pandapatan, Alican M.; Mangondato, Fahima C.; Macarimbang, Farhana A. (Jurnal Sosiologi Dialektika, 2025)
Sociology through literature of Lewis Coser inspired this study to thematically identify social conditions of Bangsamoro people using the literary works published online. Four volumes were gathered form Bangsamoro Literary Review from 2021 to 2023. The method is qualitative and thematic analysis was used to interpret and dissect the gathered literatures. Graphics or non-text form published in the journal was not included. Two levels were employed in thematic analysis: macro level (Lewis Coser) and micro level (Carter & Carter). It was revealed in the study that among twenty themes at macro level, thirteen themes emerged namely: culture, social control, socialization, self and other, status and role, sex and roles, total institutions, urban sociology, poverty, family religion, collective behavior, and, deviance. At micro level, optimism/pessimism, ambition, betrayal/revenge, curiosity/apathy, and, doubt/certainly depicted in the literary works studied. The lived experiences of Bangsamoro as one region shared common dilemmas encountered by most Filipinos such as poverty, family trust, dreaming big, safety, love affairs, and city-life. On the other hand, specific conditions from the narratives of writers as Bangsamoro are the marriage agreement, identity role, discrimination, strict religious beliefs, and others. Furthermore, literature unveils social conditions which can serve as sociological data to explore social structures and dynamics. This leads to a more comprehensible image of the extant culture, behavior, and local knowledge on particular groups.